Proceedings of the Workshop on Multiword Expressions Identifying and Exploiting Underlying Properties - MWE '06 2006
DOI: 10.3115/1613692.1613697
|View full text |Cite
|
Sign up to set email alerts
|

Using information about multi-word expressions for the word-alignment task

Abstract: It is well known that multi-word expressions are problematic in natural language processing. In previous literature, it has been suggested that information about their degree of compositionality can be helpful in various applications but it has not been proven empirically. In this paper, we propose a framework in which information about the multi-word expressions can be used in the word-alignment task. We have shown that even simple features like point-wise mutual information are useful for word-alignment task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In order to improve the word alignment quality, Venkatapathy and Joshi (2006) reported a discriminative approach to use the compositionality information of verb-based multi-word expressions. Pal et al (2011) discussed the effects of incorporating prior alignment of MWE and NEs directly or indirectly into Phrase-based SMT systems.…”
Section: Bilingual Mwe In Mtmentioning
confidence: 99%
“…In order to improve the word alignment quality, Venkatapathy and Joshi (2006) reported a discriminative approach to use the compositionality information of verb-based multi-word expressions. Pal et al (2011) discussed the effects of incorporating prior alignment of MWE and NEs directly or indirectly into Phrase-based SMT systems.…”
Section: Bilingual Mwe In Mtmentioning
confidence: 99%
“…A lexicon, including multiword expressions (MWEs), is a very important resource for many natural language processing (NLP) applications, such as building ontologies [1], information retrieval (IR) [2], text alignment [3], machine translation [4,5], and so on [6]. In general, extracting bilingual lexicons requires many linguistic resources, such as bilingual corpora (i.e., parallel or comparable), bilingual seed dictionaries, and some heuristics, for mapping identical word pairs between two languages.…”
Section: Introductionmentioning
confidence: 99%
“…While the explicit identification of multiword expressions ("MWEs": , Baldwin and Kim (2009)) has been shown to be useful in various NLP applications , recent work has shown that automatic prediction of the degree of compositionality of MWEs also has utility, in applications including information retrieval ("IR": Acosta et al (2011)) and machine translation ("MT": Weller et al (2014), Carpuat and Diab (2010) and Venkatapathy and Joshi (2006)). For instance, Acosta et al (2011) showed that by considering non-compositional MWEs as a single unit, the effectiveness of document ranking in an IR system improves, and Carpuat and Diab (2010) showed that by adding compositionality scores to the Moses SMT system (Koehn et al, 2007), they could improve translation quality.…”
Section: Introductionmentioning
confidence: 99%